A New and Practical Method for Transmission Electron Microscopy Analysis of Proteus mirabilis - Gazel, Deniz; Erinmez, Mehmet; Demirbakan, Hadiye; Ballı, Ebru; Yılmaz, Banu Coşkun (European Journal of Therapeutics, 2023)
-